(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-55-64 In the article the interior design discourse is identified and characterized through a set of typological features as a hybrid topically determined formation that combines contaminated characteristics of personality and institutionality and interacts with media discourse in media texts. It has a special linguo-semiotic system, including nominative, locative, instrumental, processive, quantitative and qualitative signs, which denote performers and customers, real estate objects, premises, meant for various purposes, their parts, furniture, materials, decorative and functional accessories, describe the creation and application of the projects, estimate the size and scale, evaluate the interior, its details, designers, events, ideas and their implementation. The methods of distributional, contextual, discursive, and intentional analysis applied to the extensive language material from the English language publications mostly in the specialized internet journals help to reveal the variability of the six above mentioned classes of verbal signs in the English interior design media discourse. The research shows that language signs denoting realities of the corresponding sphere interact with each other in the utterance to highlight different projects, trends, events and news of interior design, thus informing the readers, advertising products and services, attracting potential clients, increasing interest in this area by influencing the emotions and mood of readers and forming public opinion. The popular topics reflected in the linguosemiotic system of the interior design media discourse are celebrities’ luxurious property, nature-saving technologies, environmentally friendly materials, interior renovation with minimum costs, original and ergonomic solutions, practical advice from experts. The results of the research contribute to the development of the semiotic approach in the discourse study. Key words: interior design discourse, interior design media discourse, linguosemiotics, linguistic sign